Mapping Adolescent Cyberbullying in Wetland Communities: An Ecological Analysis Based on Bronfenbrenner’s Theory - Nina Permata Sari; Muhammad Andri Setiawan; Eklys Cheseda Makaria; Hendro Yulius Suryo Putro; Daniar Gunawan Saputra; Pramudya Ananda (Universitas PGRI Yogyakarta, 2026)
This research is important because the increasing cases of cyberbullying among adolescents, particularly vocational high school students in wetland communities, pose serious risks to their psychological Well-being and social relationships. The study aims to map the characteristics, influencing factors, and interaction patterns within adolescents’ social systems in cases of cyberbullying, using Bronfenbrenner’s ecological theory. A total of 798 vocational students in South Kalimantan participated in the study. Data were collected using a Likert-scale questionnaire grounded in five ecological systems, validated through expert review and Exploratory Factor Analysis (KMO > 0.5; factor loading > 0.5), with Cronbach’s Alpha > 0.70. Data were analysed using SPSS 25 with descriptive, correlation, and factor analyses. The findings reveal that the microsystem, particularly peer relationships and social media interactions, is the most dominant determinant of cyberbullying behaviour in wetland communities. Keywords: cyberbullying prevention, digital literacy education, quality education, peaceful and inclusive societies